Static hazards of container filling. Issue 4 (15th October 2021) - Britton, Laurence G.; Walmsley, Harold L.
Abstract: The maximum filling rates recommended by IEC and NFPA for conductive intermediate bulk containers (IBC) conflict with each other and take no account of the filling pipe diameter. A model previously developed to predict maximum liquid surface potentials in medium tanks was re‐derived using analytical approximation rather than curve fitting techniques and modified for application to conductive containers. Physically consistent flow rate limits are given for all sizes of container. Relative to the 25 kV hazardous potential threshold, IEC's flow velocity limit of 2 m/s theoretically provides a large safety factor for IBC filling that increases linearly from 2 to 5 as the inside diameter of the filling pipe decreases from 78 to 27 mm. However, because potential varies with the inverse cube of pipe diameter, the safety factor provided by NFPA's flow rate limit of 225 L/min diminishes from 8 to 1/2 over the same range and surface potentials exceed 25 kV for filling pipe diameters below about 35 mm. The model is extended to address elevated dielectric constants and practical guidance is provided for different filling pipe options. We also warn of specific practices that could increase the likelihood of a fire or explosion.